Predicted Conversational Speech: Accuracy and Epistemic Markers - Jahiu, Edona (International Journal of Linguistics and Translation Studies, 2023)
This paper analyzes prediction of speech in conversational interaction realized by informants aged 21-27, which in our context expresses possible future utterances of subjects acquainted with each other. The data is compiled by recorded spoken interaction and interview, where 37 respondents projected utterances that would be said in a certain topic or context by their bestfriend, colleague, crush or a person of certain profession. In total, 1102 options were articulated. When they resulted in coherence with their friend’s, sister’s or colleague’s response (after confirmation through telephone), they stressed the high level of mutual recognition and possibility of psycho-social perception of a person to serve as source for predicting future utterances. Therefore, it is concluded that accurate prediction is highly based on the density of pre-communication, episodic memory of conversations with that person in certain topics, epistemic stance/authority, habitual linguistic behaviors etc. There are found variety of pragma-linguistic manners in which the speaker shows her/his version of what someone else would say. Higher scale of accuracy has been noticed at family members and close friends.